1985
DOI: 10.1128/mcb.5.8.2090
|View full text |Cite
|
Sign up to set email alerts
|

RNA-mediated gene duplication: the rat preproinsulin I gene is a functional retroposon.

Abstract: Rats and mice have two, equally expressed, nonallelic genes encoding preproinsulin (genes I and II). Cytological hybridization with metaphase chromosomes indicated that both genes reside on rat chromosome 1 but are approximately 100,000 kilobases apart. In mice the two genes reside on two different chromosomes.DNA sequence comparisons of the gene-flanking regions in rats and nmice indicated that the preproinsulin gene I has lost one of the two introns present in gene II, is flanked by a long (41-base) direct r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
145
1

Year Published

1987
1987
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 229 publications
(149 citation statements)
references
References 37 publications
3
145
1
Order By: Relevance
“…The insulin I gene duplication is believed to have resulted from the integration of a cDNA produced by viral reverse transcription of an aberrant insulin II mRNA in a murine ancestor (30). We speculate that inefficient splicing of intron 1, such as we have observed, could explain why intron 1 was retained in the template mRNA.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…The insulin I gene duplication is believed to have resulted from the integration of a cDNA produced by viral reverse transcription of an aberrant insulin II mRNA in a murine ancestor (30). We speculate that inefficient splicing of intron 1, such as we have observed, could explain why intron 1 was retained in the template mRNA.…”
Section: Discussionmentioning
confidence: 64%
“…The length of intron 2 varies widely among species, but intron 1 is generally small (118 bp in mouse insulin II to 179 bp in human). Most species have a single insulin gene; but in rats and mice, a duplication has resulted in a second copy of the insulin gene that lacks the second intron (11)(12)(13). The ancestral and duplicate genes are termed insulin II and insulin I, respectively.…”
mentioning
confidence: 99%
“…Analysing structural features of the gene encoding insulin, Soares et al reported that Ins1 was generated by an RNA-mediated duplication-transposition event involving a transcript of Ins2 [1]. In addition, only Ins2 is expressed in the NOD thymus with both genes expressed in islet beta cells [3,16,17].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Ins1 lacks an intron present in Ins2. These structural features suggest that Ins1 was generated by an RNA-mediated duplication-transposition event involving a transcript of Ins2, which was reinserted into the genome (retroposon) [1].…”
Section: Introductionmentioning
confidence: 99%
“…Unlike most species, rats possess two non-allelic insulin genes which are highly homologous within the protein coding sequences; this homology extends approx. 500 bp upstream from the cap site of the messenger RNA [7]. The rat insulin I gene, which has lost one of the two intervening sequences present in the rat insulin II gene, is believed to have arisen via an RNAmediated transposition event from a transcript which was initiated upstream from the normal initiation site of the rat insulin II gene [7].…”
Section: Introductionmentioning
confidence: 99%